2012
DOI: 10.1121/1.4770058
|View full text |Cite
|
Sign up to set email alerts
|

Applying automatic aural classification to cetacean vocalizations

Abstract: Passive acoustic methods are widely used to detect and classify marine mammals; however, these passive sonar systems are often triggered by other transient sources, producing many false alarms. Additionally, to positively identify marine mammals, large volumes of data are collected that need to be processed by a trained analyst. To reduce acoustic analyst workload, an automatic detector can be implemented that produces many detections, which feed into an automatic classifier that significantly reduces the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…A supervised learning algorithm then maps these attributes to a call class after learning training examples labeled by human analysts. Classifier of this kind include aural classification [27], neural networks [3], hidden Markov models [28], quadratic discriminant function analysis [29], Gaussian mixture models [30] or classification trees [31]. More recently, Halkias et al [25] proposed an alternative approach based on hybrid generative/discriminative models commonly used in machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…A supervised learning algorithm then maps these attributes to a call class after learning training examples labeled by human analysts. Classifier of this kind include aural classification [27], neural networks [3], hidden Markov models [28], quadratic discriminant function analysis [29], Gaussian mixture models [30] or classification trees [31]. More recently, Halkias et al [25] proposed an alternative approach based on hybrid generative/discriminative models commonly used in machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…Previous effort has shown that a prototype aural classifier developed at Defence R&D Canada [1] can be used to successfully discriminate cetacean vocalizations from several species; bowhead, humpback, North Atlantic right, and sperm whales vocalizations have been classified in this way [2]. To achieve these accurate results, the aural classifier employs perceptual signal features, which model the features used by the human auditory system.…”
Section: Introductionmentioning
confidence: 99%
“…Like the human auditory system, the perceptual features used by the aural classifier can be employed to classify sounds from different sources, e.g. active sonar echoes [1] and cetacean vocalizations [2]. Thus, the aural classifier has proven to be very robust in its applicability to different data sources.…”
Section: Introductionmentioning
confidence: 99%
“…Em geral são usados métodos baseados na correlação (Abbot et al, 2010;Mellinger, 2004;Mellinger et al, 2011;Nanaware et al, 2014), redes neurais (Dugan et al, 2010;Mellinger and Clark, 2000), métodos estatísticos multivariados (Binder and Hines, 2012;Diaz Lopez, 2011), dentre outros. Esses métodos supõem que amostras do padrão do evento acústico de interesse sejam conhecidas e estejam disponíveis.…”
Section: Métodos De Detecçãounclassified